Experiential Learning Intervention Through Outbound Activity Enhancement on Emotional Intelligence, Competitiveness, and Physical Fitness of Female Workers - Ayuning Maharesti; Berliana; Mustika Fitri; Komarudin (Universitas Negeri Semarang, 2025)
In the era of global competition, the development of professional competencies of female workers faces specific challenges that require innovative approaches. This study aims to analyze the effectiveness of experiential learning interventions through outbound activities in improving emotional intelligence and competitiveness of female workers. This study is motivated by the need of Daya Group Honda to develop female workers into division leaders in branches spread across West Java through the DBMP (Daya Basic Management Program). This study uses an experiential learning approach applied in outbound activities as a learning method through direct experience followed by structured reflection. Outbound activities were chosen because they offer a comprehensive framework for developing cognitive, emotional, and physical aspects simultaneously in a structured outdoor environment. This study involved 16 female employees from Daya Cipta Motor Group Honda Bandung who participated in a two-week experiential learning program through outbound activities. Data were collected using standardized questionnaires on emotional intelligence and competitiveness and analyzed using the Wilcoxon test. The results revealed a significant improvement in emotional intelligence, while competitiveness showed no significant change. Theoretically, this study reinforces the development of Experiential Learning theory in the context of female human resource development. Practically, the findings provide valuable insights for the Ministry of Manpower and company management in formulating effective, evidence-based training programs that enhance emotional intelligence and promote sustainable competitiveness among female workers. The formulation of the research problem includes two main aspects: (1) the effect of experiential learning interventions through outbound activities on emotional intelligence of female workers, (2) the effect on competitiveness of female workers.